Challenges in transcatheter aortic valve implantation (Swiss Medical Weekly, 2012)
Although safety and efficacy of TAVI was improved with next-generation equipment, experience, and careful patient selection, some worrisome complications associated with the procedure remain. Current hot topics in transcatheter aortic valve implantation include patient selection, valve sizing, paravalvular regurgitation, cerebrovascular accidents, vascular complications and need for a permanent pacemaker. In this article we review the pathophysiology, avoidance and treatment options for these complications.